Choice of Initial Alignment Archwires in Moderate to Severe Crowding in Patients Treated with Damon and MBT Systems: A Retrospective Study - Anjali Anna Thomas1 , Remmya Mary Varghese2 , Remmya Mary Varghese3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Initial arch wires are the firsts arch wires to be inserted into the fixed appliance at the beginning of orthodontictreatment and are used mainly for the alignment of teeth by correcting crowding and rotations. With anumber of different types of orthodontic arch wires available for initial tooth alignment, it is importantto understand which wire is most efficient. The purpose of this study was to evaluate the choice of initialalignment archwires in treating patients with moderate to severe crowding with the MBT and Damonappliances. Sample included 50 patients aged 18 years and above,selected from the pretreatment recordsof the patients reported to the Department of Orthodontics,Saveetha Dental College,Chennai.Results ofthe study was obtained by evaluating the initial archwires used in case of MBT and Damon appliances.This study revealed that 85.7% out of the 35 MBT cases used 0.014 NiTi as the initial archwire and all ofthe Damon cases started with 0.013 CuNiTi.The collected data were entered into an Excel sheet(MicrosoftExcel 2007) and statistical analysis done. The association between gender and initial alignment archwiresin moderate to severe crowding cases was found using Chi-square association test in IBM SPSS software,which showed a statistically not significant difference (p -value >0.05) , hence there is no gender differencein the choice of initial alignment archwires in moderate to severe crowding patients.